If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4 + 9w) = 26w (4 * 2 + 9w * 2) = 26w (8 + 18w) = 26w Solving 8 + 18w = 26w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-26w' to each side of the equation. 8 + 18w + -26w = 26w + -26w Combine like terms: 18w + -26w = -8w 8 + -8w = 26w + -26w Combine like terms: 26w + -26w = 0 8 + -8w = 0 Add '-8' to each side of the equation. 8 + -8 + -8w = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -8w = 0 + -8 -8w = 0 + -8 Combine like terms: 0 + -8 = -8 -8w = -8 Divide each side by '-8'. w = 1 Simplifying w = 1
| (w+2)(2w-1)=0 | | 2*8+3*-9= | | 3.45*4-8.18= | | 8m-5=(3m+5) | | 3.45(4)-8.18(1)= | | 3+3*6+2=-17 | | 500*98+x*0=(500+x)*30 | | 6n+3-5=-1 | | 6y+814=1186 | | cos(20)=(9/x) | | 32/-7 | | 4(1/4) | | 3x+10y=-15 | | F^2-22f+72=0 | | (5-8w)(5+8w)= | | 12-9y=-5 | | -7x+6-9=29 | | -4+3=-12+17x | | 3z/10-5=8 | | 5(2b-3)=3(b+9) | | 12(12n)+n-3=396 | | 1/8-X/7=3/56 | | F^2-22f=72 | | -4(1-7z)=-29 | | 5x-2/3=-49/10 | | 15x^4-15x^3=0 | | Z/7-2=6 | | f(x)=x^4+32 | | 8(p-a)-6=2(ap-5) | | 6x+7y(2-3y)=-21 | | 24x+9=21 | | 5x-7=4x-7 |